CD ADSORPTION ONTO BACTERIAL SURFACES: A UNIVERSAL ADSORPTION EDGE? - Yee N.; Fein J. (My University, 2001)
In this study, we measure the thermodynamic stability constants for proton and Cd binding onto the Gram-negative bacteria Escherichia coli and Pseudomonas aeruginosa, and the Gram-positive bacteria Bacillus megaturium, Streptococcus faecalis, Staphylococcus aureus, Sporosarcina ureae, and Bacillus cereus. Potentiometric titrations and Cd-bacteria adsorption experiments yield average values for the carboxyl site pKa, site concentration, and log stability constant for the bacterial surface Cd-carboxyl complex of 5.0, 2.0 x 10-3 mol/g and 4.0 respectively. Our results indicate that a wide range of bacterial species exhibit nearly identical Cd adsorption behavior as a function of pH. We propose that metal-bacteria adsorption is not dependent on the bacterial species involved, and we develop a generalized adsorption model which may greatly simplify the task of quantifying the effects of bacterial adsorption on dissolved mass transport in realistic geologic systems.